Electromyography in the horse: A useful technology - Williams, J. M. (Journal of Equine Veterinary Science, 2018)
Highlights: • Surface, fine-wire, and needle electromyography (EMG) have been used in equine research. • Surface EMG is less invasive but only records superficial muscle activity. • Electromyography can be applied in the horse to determine muscle recruitment and fatigue. • An equine-adapted version of the Surface EMG for Non-Invasive Assessment of Muscle guidelines would improve equine EMG research. • Grounded and strong within-subjects research designs should be used in equine EMG research.